Complexities of oral antiplatelet drugs use in pregnancy - Antonijević Nebojša M.; Gošnjić Nikola D.; Ranković Ivan V.; Jovanović Ljubica M.; Veljić Ivana D.; Matić Dragan M.; Kočica Mladen J.; Karadžić-Kočica Milica M.; Terzić Branka M.; Leković Žaklina V.; Jelić Dario D.; Kanjuh Vladimir I. (Srpsko lekarsko drustvo, 2020)
Introduction: Given the increasing occurrence of pregnancy at a relatively older age in the current clinical practice, many therapeutic approaches characteristically used in the elderly population are becoming an important consideration point for the clinicians. Antiplatelet drugs: The safety of antiplatelet drug administration in pregnancy should be brought into a sharper focus regarding both mother and child. It is a complex clinical task since the pregnancy is followed by many changes potentially affecting the drug choice - increased blood coagulability, changes in platelet aggregation, and pharmacokinetic alternations of the drug itself. Acetylsalicylic acid, as the most commonly used antiplatelet drug, appears to be mostly safe and effective for mother and fetus in many conditions occurring during pregnancy when used in low doses. However, although considered generally safe, its use requires careful approach due to many drug and pregnancy specificities. On the other hand, evidence showing adequate clinical use of P2Y12 receptor antagonists (clopidogrel, ticagrelor, prasugrel, and ticlopidine) are scarce. Cases showing their use in clinical practice are emerging and the future practice and treatment approach might be changed with the new cases becoming available. Conclusion: Regardless of the drug, pregnancy itself and any indication for the treatment used in this patient population are typically complex and require well-coordinated management by the interdisciplinary clinical team.